Reviving Organizational Commitment: The Role of Job Satisfaction, Transformational Leadership, and Work-Life Balance - Suseno, Bambang; Dewi, Mustika (Nomico, 2024)
The research's objective is to test the influence of transformational leadership and work-life balance on organizational commitment by adding mediation variables such as job satisfaction. This research uses a quantitative approach with numerical data. This research method involves descriptive surveys and explanatory surveys. The study collected data from approximately 45 teachers at Maitreyawira's private high school. Sampling technique with a saturated sample. The result of this research is that transformational leadership and work-life balance influence organizational commitments. Theoretically, the results of this study confirmed that it was strategically implemented to maintain organizational commitment, and the findings broadened our understanding of the factors affecting organizational communities and job satisfaction. The practical benefits of this research, particularly for an organization operating a full-day school system, include the need to adopt a transformational leadership style and maintain a work-life balance to ensure teacher loyalty.